Step 1
To find x-intercept, make x subject of the relation
3x + 6y = 54
3x = -6y + 54
Divide through by 3
![\begin{gathered} (3x)/(3)\text{ = }(-6y)/(3)\text{ + }(54)/(3) \\ x\text{ = -2y + 18} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/josxygzoxcgo9jm9phy5w8yczwvks2xkap.png)
Therefore x intercept from x = my + c
c is the intercept
Therefore, x intercept = 18
To find x-intercept, make x subject of the relation
3x + 6y = 54
6y = -3x + 54
Divide through by 6
![\begin{gathered} (6y)/(6)\text{ = }(-3x)/(6)\text{ + }(54)/(6) \\ y\text{ = }(-x)/(2)\text{ + 9} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8t70u4zhjnkng0xmgkv6xxknedqzdv8ps1.png)
Therefore y-intercept from y = mx + c
c is the intercept
Therefore, y-intercept = 9